Market coverage of wood imports by the EU Timber Regulation - Holger Weimar; Niels Janzen; Matthias Dieter (Johann Heinrich von Thünen-Institut, 2015)
Illegal Logging is one of the major global causes for deforestation and the degradation of forests. The further manufacturing of illegally logged wood and products made thereof as well as the associated trade has also negative social and economic effects on both sides of the wood markets, the producer and consumer countries. One of the key measures of the European Union (EU) to combat illegal logging is the EU Timber Regulation (EUTR). The EUTR came into effect on March 1, 2013 and it prohibits the placing of wood and wood products made of illegally logged wood on the EU internal market. This placement can either be done by selling removals from European forests or by importing wood and wood-based products into the EU. But for what kind of products does the regulation apply exactly? The EUTR refers to its An-nex where a list is provided with respective commodities. The products are structured ac-cording to the trade classification of the Combined Nomenclature (CN). The main focus is laid on wood and articles of wood (chapter 44 of the CN), on pulp of wood (chapter 47) and on paper and paperboard and articles made thereof (chapter 48). Additionally commodity codes for furniture and one code for prefabricated buildings are listed. However, as certain wood-based products are not included in the EUTR, the question arises, how many wood-based products are not covered by the EUTR. What is the coverage ratio of the EUTR if we are looking at all wood-based products? [...]
urn:nbn:de:gbv:253-201508-dn055557-8
Keywords: 630; EUTR; coverage ratio; wood-based products; illegal logging; international trade; reference units